Chewing versus Swallowing Ticagrelor to Accelerate Platelet Inhibition in Acute Coronary Syndrome - the CHEERS study - Asher, Elad; Frydman, Shir; Katz, Moshe; Regev, Ehud; Sabbag, Avi; Mazin, Israel; Abu-Much, Arsalan; Kukuy, Andrew; Mazo, Anna; Erez, Aharon; Berkovitch, Anat; Narodistky, Michael; Barbash, Israel; Segev, Amit; Beigel, Roy; Matetzky, Shlomi (Thrombosis and Haemostasis, 2017)
It was the study objective to evaluate whether chewing a 180 mg loading dose of ticagrelor versus an equal dose of traditional oral administration, enhances inhibition of platelet aggregation 1 hour (h) after administering a ticagrelor loading dose in non-ST elevation myocardial infarction (NSTEMI) patients. Dual anti-platelet therapy represents standard care for treating NSTEMI patients. Ticagrelor is a direct acting P2Y12 inhibitor and, unlike clopidogrel and prasugrel, does not require metabolic activation. Fifty NSTEMI patients were randomised to receive either a chewing loading dose of 180 mg ticagrelor or an equal standard oral dose of ticagrelor. Platelet reactivity was evaluated by VerifyNow at baseline, 1 and 4 h post-loading dose. Results are reported in P2Y12 reaction units. Patients then continued to receive standard 90 mg oral ticagrelor twice daily. Baseline characteristics did not differ between the two groups. P2Y12 reaction units in the chewing group compared with the standard group at 0, 1 and 4 h after ticagrelor loading dose were: 245 vs 239 (p=0.59), 45 vs 130 (p=0.001) and 39 vs 60 (p=0.12), respectively, corresponding to a relative inhibition of platelet aggregation of 83 % vs only 47 % at 1 h (p< 0.001), and 84 % vs 77 % (p=0.59) at 4 h. Major adverse cardiac and cardiovascular events at 30 days were low (2 %), occurring in only one patient in the standard group. In conclusion, chewing a 180 mg ticagrelor loading dose is feasible and facilitates both faster and improved early inhibition of platelet aggregation in NSTEMI patients, compared with a standard oral-loading dose.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Chewing ticagrelor; acute coronary syndromes; inhibition of platelet aggregation